2017
DOI: 10.1159/000481346
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Assessment of Gastric Xanthoma as Potential Predictive Marker of Gastric Cancer

Abstract: Background/Aims: Gastric xanthomas are frequently observed in the stomach as small yellowish plaques or nodules. A close relationship among Helicobacter pylori infection, atrophic gastritis, and xanthomas has been reported. We assessed the clinicopathological features of gastric cancer with or without xanthomas. Methods: A total of 91 patients who were diagnosed as having early gastric cancer were enrolled. We evaluated the gastritis status using scores for gastritis and atrophy, positivity of H. pylori infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
5
13
1
Order By: Relevance
“…Body findings, such as body xanthoma and RHG probably denoted hypoacidity derived from active inflammation, similar to the report previously published [ 20 , 21 ]. Body diffuse erythema means interstitial inflammatory cell infiltration in the atrophy background [ 11 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Body findings, such as body xanthoma and RHG probably denoted hypoacidity derived from active inflammation, similar to the report previously published [ 20 , 21 ]. Body diffuse erythema means interstitial inflammatory cell infiltration in the atrophy background [ 11 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…GX has received little clinical attention, perhaps because it is considered a benign entity (15). A retrospective cohort study reported that the presence of GX was significantly associated with the presence of GC (13, 14). Another cohort study reported that the presence of GX was a useful marker for predicting the development of GC by performing follow-up EGD (15).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding why GC develops more frequently in patients with GX than in those without GX, the increased release of oxygen free radicals may be involved in the formation of GX (22). Conversely, the presence of GX may reflect the severity and long duration of chronic gastritis (14), a risk factor for the development of GC. In fact, the proportion of patients with atrophy (open type) and the atrophy score of patients were significantly higher in Group C than in Group NC.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Atrophy-matched control analysis was singled out and the incidence of gastric xanthelasma has been shown to be significantly higher in patients with diabetes mellitus. 3,4,7 The diagnosis should be confirmed in order to eliminate the possibility of gastric malignancy. 8 In our case, xanthoma was diagnosed in an elderly male patient, where erythematous gastropathy was present.…”
Section: Discussionmentioning
confidence: 99%